Regenerative organic rankine cycle as bottoming cycle of an industrial gas engine traditional and advanced exergetic analysis (2020)
This investigation shows a traditional and advanced exergetic assessment of a waste heat recovery system based on recuperative ORC (organic Rankine cycle) as bottoming cycle of a 2 MW natural gas internal combustion engine. The advanced exergetic evaluation divides the study into two groups, the avoidable and unavoidable group and the endogenous and exogenous group. The first group provides information on the efficiency improvement potential of the components, and the second group determines the interaction between the components. A sensitivity analysis was achieved to assess the effect of condensing temperature, evaporator pinch, and pressure ratio with net power, thermal efficiencies, and exergetic efficiency for pentane, hexane, and octane as organic working fluids, where pentane obtained better energy and exergetic results. Furthermore, an advanced exergetic analysis showed that the components that had possibilities of improvement were the evaporator (19.14 kW) and the turbine (8.35 kW). Therefore, through the application of advanced exergetic analysis, strategies and opportunities for growth in the thermodynamic performance of the system can be identified through the avoidable percentage of destruction of exergy in components.